THE CRITICAL ROLE OF KNOWLEDGE SHARING ACTIVITY AND INTERGENERATIONAL CONFLICT SOLUTION TO CREATE FAMILY BUSINESS SUSTAINABILITY: INTERGENERATION RELATIONSHIP QUALITY AS MODERATING - Liliana Dewi; Elia Ardyan (International Journal of Accounting, Finance and Business, 2020)
This study aims to examine the important role of knowledge sharing activities andintergeneration solutions in order to create family business sustainability. This research alsoexamines the moderating impact of intergeneration relationship quality. Respondents in thisstudy were 213 business owners of Batik SMEs in Central Java. Respondents are fromgeneration 2-4 of the family business. Data were analysed using SEM-PLS. The results of thisstudy indicate that knowledge sharing activities and intergeneration conflict solutions are ableto create family business sustainability. This research also found that a quality relationshipbetween parent and child is able to moderate the influence of knowledge sharing activity andintergeneration conflict solution. This study contributes to theoretical and managerialcontributions regarding sustaining family businesses.